2021
DOI: 10.1016/j.jbc.2021.100869
|View full text |Cite|
|
Sign up to set email alerts
|

Schizosaccharomyces pombe Ppr10 and Mpa1 together mediate mitochondrial translational initiation

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…100 Tandem affinity purification (TAP) of Ppr10 recovered every mt-mRNAs, several mt-LSU and mt-SSU proteins and a novel nuclear-encoded, mitochondrial-localised protein Mpa1. 65,101 Consistently, both Ppr10 and Mpa1 cosedimented with the assembled mitoribosome. Deletion of the two central PPR motifs in Ppr10 compromised its interaction with Mpa1.…”
Section: Three Ppr Proteins Are Important For S Pombe Mitochondrial T...mentioning
confidence: 71%
See 2 more Smart Citations
“…100 Tandem affinity purification (TAP) of Ppr10 recovered every mt-mRNAs, several mt-LSU and mt-SSU proteins and a novel nuclear-encoded, mitochondrial-localised protein Mpa1. 65,101 Consistently, both Ppr10 and Mpa1 cosedimented with the assembled mitoribosome. Deletion of the two central PPR motifs in Ppr10 compromised its interaction with Mpa1.…”
Section: Three Ppr Proteins Are Important For S Pombe Mitochondrial T...mentioning
confidence: 71%
“…In addition, Ppr10 co‐immunoprecipitated with the mitochondrial translation initiation factor Mti2 (discussed above). Upon either ppr10 or mpa1 deletion, Mti2 (and Mti3) no longer co‐sedimented with the mt‐SSU 101 . Taken together, these data suggested that Ppr10 and Mpa1 cooperatively enhance mitochondrial translation initiation, by physically connecting Mti2 and Mti3 to the mt‐SSU.…”
Section: Mitochondrial General Translation Factorsmentioning
confidence: 91%
See 1 more Smart Citation
“…Mitochondrial proteins were separated using SDS‐PAGE and then electrophoretically transferred to nitrocellulose membranes. The membrane was probed with rabbit polyclonal antibodies (Abs), which were produced as described (Luo et al, 2021; Wang et al, 2017). The secondary Ab used was IRDye 800CW‐conjugated goat anti‐rabbit Abs (LI‐COR Biosciences).…”
Section: Methodsmentioning
confidence: 99%
“…In S. pombe , PPR protein Ppr2 is required for overall mitochondrial protein synthesis (Kuhl et al, 2011). Ppr10 forms a complex with the translation activator Mpa1 and plays a role in the initiation of mitochondrial protein translation by promoting the binding of the mitochondrial translation initiation factors Mti2 and Mti3 to the small subunit of the mitoribosome (Luo et al, 2021; Wang et al, 2017). In humans, leucine‐rich PPR‐containing protein (LRPPRC) is required for the polyadenylation and translation of mitochondrial mRNAs (mt‐mRNAs) with its partner SRA stem‐loop interacting RNA‐binding protein (SLIRP) (Chujo et al, 2012; Ruzzenente et al, 2012; Sasarman et al, 2010).…”
Section: Introductionmentioning
confidence: 99%